Zmiany w ustawach małżeńskich Augusta za panowania dynastii julijsko-klaudyjskiej - Zabłocka, Maria (Prawo Kanoniczne, 1987)
Under the reign of Augustus’ successors both lex Iulia et Papia as well as lex Iulia de adulteriis coercendis were subject to changes. Lex Iulia et Papia imposed an obligation to remain in the state of matrimony for men and women until a certain age limit; if the men were past this age limit negative consequences of avoiding the binding orders came no longer into consideration. SC Pernicianum extended the said consequences over people well advanced in years who earlier had not met the requirements of the law. SC Claudianum attempted at softening the sternness of the changes but only in relation to men since according to SC Calvisianum women were excluded from it. However, the reasons for enacting these SC seem to have departed from the intensions propagated by Augustus. New regulations aimed at only fiscal reasons and partially (SC Claudianum) personal situation of the Princeps. Application of lex Iulia de adulteriis was also gradually changed. Tiberius increased the punishability of facts recognized as crimes by the act and extended its application over new facts. Whereas Caligula abrogated punishability of facts falling under the notion of lenocinium and imposed taxes on them instead.